EVALUASI PROGRAM PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA BALITA UNDERWEIGHT DI WILAYAH KERJA PUSKESMAS BANDARHARJO, KOTA SEMARANG - Abdul Hakim Adriansyahi; Galuh Ramaningrum; Hema Dewi Anggraheny (PT. Hasba Edukasi Mandiri, 2026)
Background: Underweight in toddlers remains a nutritional problem in Indonesia, including in the Bandarharjo Community Health Center (Puskesmas) area, which has a higher rate than surrounding areas. The implementation of the Supplementary Feeding Program (PMT) still faces various obstacles, necessitating an evaluation of its relationship to changes in the nutritional status of underweight toddlers. This study aims to analyze the relationship between PMT consumption and changes in the nutritional status of underweight toddlers in the Bandarharjo Community Health Center area, Semarang City. Methods: This study is a quantitative study with an observational analytical design using a cross-sectional approach. The subjects were underweight toddlers aged 6–24 months who were still following PMT in the working area of the Bandarharjo Community Health Center, Semarang City. A total of 36 respondents were selected using a purposive sampling technique. Data collection was carried out through interviews, questionnaires, anthropometric measurements, and secondary data review. Data were analyzed univariately to describe the characteristics of the respondents including child age, gender, parental education level, parental income, history of exclusive breastfeeding, history of low birth weight (LBW), PMT consumption, and changes in toddler nutritional status based on the BB/U indicator. Bivariate analysis was conducted to assess the relationship between PMT consumption as an independent variable and changes in nutritional status as a dependent variable using the Chi-square test with the help of SPSS software at a significance level of p < 0.05. Results: The majority of respondents, 19 children, consumed PMT with less than ½ portion remaining (52.8%). The nutritional status of toddlers showed improvement after the intervention, there was an increase in nutritional status before and after PMT administration, namely 69.4% of toddlers showed a BB/A z-score value that was in the normal nutritional status category after the intervention and a decrease in the proportion of underweight from 88.9% to 19.4%. However, the results of the analysis showed that the relationship between PMT consumption and changes in nutritional status was not statistically significant (p = 0.078). Conclusion: The relationship between PMT consumption and changes in nutritional status was not statistically significant, so other supporting efforts are needed, such as nutritional education for parents and more optimal monitoring of PMT consumption.